Interview with Ali Ahmad Jalali - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2011)
For this issue on understanding armed groups, the Review considered it important to invite someone who could give the inside perspective of an armed group. Minister Ali Ahmad Jalali, currently Distinguished Professor at the National Defense University in Washington, DC, is uniquely placed to do so in the context of Afghanistan: he has at once the experience of a former member of the Mujahideen during the war against the Soviet Union, a former Colonel in the Afghan National Army, and a former Minister of the Interior for Afghanistan from 2003 to 2005. Minister Jalali has published extensively on political, military, and security issues in Afghanistan, Iran, and Central Asia.